Narrative and narrativeA reading of Abd al-Malik Murtada's effortsin analyzing the narrative discourse (مجلة إحالات, 2026)
This research aims to provide an analytical presentation on one of themost important modern books, which discussed in depth the issues ofnarrative and narrative, and concerned with the analysis of narrative discourse, in modern and innovative ways, and by that we mean the book: “Narrative and narrative and narrative - a presentation of the theories of contemporary Arab narrative, and analyzes of some of its texts -”, by thewell-known critic Dr. Abd al-Malik Murtada; Where we meet in it a set ofdeep analyzes and distinguished scientific studies, in which the researcher discussed several issues that occupy a high position in the Arab narrative.